Impact of Artificial Intelligence on Academic Integrity: Exploring Teachers’ and Students’ Perspectives - Azeem, Asmaa; Siddiqui, Ghazal Khalid; Ali, Muhammad Shahid Zulfiqar (Journal of Development and Social Sciences, 2025)
This qualitative study has been conducted under Interpretivist paradigm to explore the teachers’ and students’ perspectives regarding the impact of Artificial Intelligence (AI) on the academic integrity in higher education. For this purpose, there were eight university teachers and eight students belonging to the social sciences selected purposively from a public university. The collected data with the help of interview protocol were analyzed by Thematic analysis. The results revealed that the teachers cited AI’s role in enabling academic dishonesty, the inadequacy of detection tools, and students’ lack of understanding of ethical boundaries. Some recognize that AI has potential as a learning tool. However, the students are confused by ethical lines that are not well defined. Some confess an over-reliance on AI, and its effect on independent learning. The institutional policies and literacy programs to empower students to leverage AI ethically, while upholding academic integrity are recommended.